Assessment of the effectiveness of Integrated Pest Management (IPM) farming approaches the case of vegetable farmer field school participants in Leon, Iloilo - Felarca, Nelly L. (University of the Philippines in the Visayas, 2005)
The study aims to assess the adoption rate of Integrated Pest Management (IPM) farming approaches, specifically to determine how effective it is in increasing producivity. Problems encountered in the adoption of the IPM farming approaches will be identified and its sustainability will be determined. A questionnaire was constructed and used in gathering the primary data. Total farmer respondents interviewed was twenty-nine, randomly selected among graduates of first vegetable Farmer Field School (FFS) conducted in five barangays of Leon, Iloilo. The Municipality of Leon, being known to be the vegetable bowl of Panay was chosen as the host municipality of the study. analysis data was done with the use of common measures of central tendencies such as frequency, mean and percentile ranking of responses was considered. Cost and Return Analysis was done in analyzing economic data. the study further revealed that male farmers (72%) were not receptive to IPM farming approaches for reason cited that it is laborious and difficult to practice for it needs time and effort. However, feedback frm other farmers was that IPM is a good farming practices but it needs skills in decision making on how to apply such management practices after monitoring was done in the field especially if problem occur. 10% of the respondent said that IPM is effective if neighbooring farms would also practice IPM so that friendly insects that control insect pests would survive if chemical usage would be reduced or ultimately be eliminated. IPM (as cited in Review of Literature) is an ecologically based pest control strategy that relies on natural science enemies and weather, and seeks out control tactics that disrupt these factors as possible. the technology uses pesticides, but only after systematic monitoring of pest populations and natural control factors indicates a need and pesticides used is green label that is safe for humans.Despite the low percentage of respondents who adopted the ipm, which is environment friendly technology, the researcher stlll, conclude that IPM farming approaches are good practices to be employed in farming. These farming approaches wuld correct our imbalance ecosystem, which will balance the insect population of natural enemies vis-a vis harmful insects that damage our crop. It would also balance our nature for the advantage of our crops and other living creature in the environment. In effect of course, applying the IPM farming approaches will produce nutritious vegetables that are safe for consumption.